Strain Induced Electronic and Optical Properties of 2D Silicon Carbide Monolayer Using Density Functional Theory - Sharma, S. B.; Adhikari, R.; Sigdel, K. R.; Bhatta, R. (Journal of Nepal Physical Society, 2021)
Using the first principle calculation, we investigated the structural, electronic, and strain-dependent optical properties of the two-dimensional hexagonal Silicon Carbide (SiC) Monolayer. We found that the biaxial compressive strain loading gradually changes the direct bandgap SiC into indirect bandgap semiconductor. The compressive strain increases the bandgap but reduces the values of static dielectric constant and refractive index. Conversely, the biaxial tensile strain loading decreases the bandgap but increases the value of static dielectric constant and refractive index. The result shows that the electronic and optical properties of SiC can be engineered to the desired value by applying strain. The large bandgap issue for the SiC monolayer is limiting its uses in different applications which can be overcome with the help of biaxial strain.